PRESIDEN MEMBAWAHKAN KEPOLISIAN NEGARA - H. Eko Sugitario (Fakultas Hukum Universitas Surabaya, 2018)
State Constitution of 1945, Republic Indonesia, herein after called Conti.titution 1945 and be concised UUD 1945. Article 10 determine that